Optimized Ginkgo biloba extract EGb 761®: boosted therapeutic benefits with minimized CYP enzyme interference - Sunbeom Kwon; Sunbeom Kwon; Suji Jeong; Suji Jeong; Seulah Lee; Seulah Lee (Journal of Pharmacy & Pharmaceutical Sciences)
ObjectThe development of cognitive-enhancing drugs from Ginkgo biloba extract is actively pursued worldwide. This study compares the chemical compositions of different G. biloba extracts and their formulated drugs, highlighting the distinguishing characteristics and potential benefits of optimized G. biloba extract, EGb 761®.MethodsWe analyzed three G. biloba extracts and fifteen formulated drugs using HPLC, principal component analysis, and LC-MS/MS to identify key compositional differences. Molecular docking analysis was conducted to evaluate the binding affinity of the key component with a target protein involved in cognitive enhancement. CYP inhibition assays were performed on selected extracts and their derived products to examine drug-drug interactions.ResultsEGb 761® and its formulated drugs displayed a unique composition, characterized by a significantly higher level of protocatechuic acid (PCA). PCA demonstrated strong interactions with the M1 receptor, acetylcholinesterase, glycogen synthase kinase-3, which are the key targets for cognitive enhancement. CYP inhibition assays indicated that EGb 761® and the drugs derived from EGb 761® had lower inhibitory activity compared to other samples.ConclusionThe high PCA content in EGb 761® may contribute to cognitive benefits. With low CYP inhibition, it suggests minimal interference with drug metabolism, highlighting its potential as a safer cognitive enhancer. Ultimately, this study indicates that the composition of EGb 761® can be effectively leveraged for its pharmacological benefits.